The role of technological innovation in environmental pollution, energy consumption and sustainable economic growth: Evidence from South Asian economies. (January 2022) - Mughal, Nafeesa; Arif, Asma; Jain, Vipin; Chupradit, Supat; Shabbir, Malik Shahzad; Ramos-Meza, Carlos Samuel; Zhanbayev, Rinat
Abstract: This study examines the causal relationship among technological innovation (TI), environment pollution (EP), energy consumption (EC) and sustainable economic growth (SEG) from selected South Asian economies. In order to identify the causal association between energy growth and nexus of CO2 emissions, this study is employed the premises of the EKC framework. This study has used annual time series data set from world development indicator (WDI), start from 1990 to 2019. The result of a fully modified ordinary least square (FMOLS) method describes a significantly worsen the quality environment in the south Asian region. The individual country as Bangladesh shows a positively significant impact on the CO2 emissions and destroying the level of environment regarding non-renewable and renewable energy and technological innovation index. However, negative and positive values of growth (GDP) and square of GDP respectively confirm the EKC hypothesis in this region. This study has identified the causality between GDP growth and carbon emission and found bidirectional causality between economic growth and energy use. Highlights: The objective of this study is to investigate the relationship among technological innovation, environment pollution, energy consumption and sustainable economic growth from selected south Asian economies. These variables are interlinked to each other, especially technological innovation plays an important role through reducing the environmental pollution and increasing economic development. In the early economic growth stages, to increase the production capacity of the economy, the environmental degradation issues are raised due to natural resource depletion. The environmental quality is significantly ignored by various countries to achieve highest economic growth in this stage. It is observed that from last couple of decades, the south Asian region has trying to overcome the issue of climate change and environmental pollution in order to increase their trade volume and sustainable economic growth rate. The study is trying to discuss environmental degradation issues due to natural resource depletion. Environmental quality has been significantly reduced by countries attempting to achieve the highest economic growth in the first stage. Beyond it, the main goal of the economies is to attain sustainable economic growth and the welfare of the economy with technological innovation (clean environmental-based technologies) and to develop environmental policies to mitigate CO2 emissions. Thus, south Asian economies wish to move from poor environmental conditions to a clean environment for sustainable economic growth. For this purpose, this study employs modern technique with latest data set for five south Asian countries namely, Bangladesh, Bhutan, India, Pakistan and Sri Lanka. This study addresses the following research questions; does the environment pollution ( CO 2 emission) reduce through modern technological innovations and increase sustainable economic growth? How energy consumption mitigates the CO 2 emission in south Asian region through technology Innovation?